Age‐related change and sex difference over 60s in disc‐fovea angle in Japanese population: the Nagahama Study. Issue 7 (25th January 2018) - Miyata, Manabu; Yoshikawa, Munemitsu; Ohtsuki, Hiroshi; Muraoka, Yuki; Hata, Masayuki; Yokota, Satoshi; Fujimoto, Masahiro; Miyake, Masahiro; Tabara, Yasuharu; Matsuda, Fumihiko; Yoshimura, Nagahisa; ,
Abstract: Purpose: To analyse the disc‐fovea angle (DFA) by age group and to compare sex differences in each age group in a large cohort population. Methods: This community‐based cross‐sectional cohort study included 9682 eyes of 9682 volunteers (aged 30–75 years). We measured the DFA, which is the angle between a horizontal line and a line connecting the fovea with the centroid of an optic disc on fundus photographs of the right eye. We manually marked the fovea and surrounded the optic disc. The centroid of an optic disc and the DFA was automatically calculated using originally developed software. We compared the DFA between age groups in 10‐year increments and investigated sex differences of DFA in each age group. Results: Overall mean DFA was 6.32 ± 3.53°. The DFA of older subjects was significantly larger than that of younger subjects (p < 0.001). The DFA of women was larger than that of men in their 60s and 70s (p < 0.001 for both), but not in subjects in their 30s, 40s and 50s. Conclusion: Larger DFA in women than in men in their 60s and 70s suggests the possibility that age‐related excyclo‐shift occurs more easily in postmenopausal women compared to men of the same age.